Engineering of Stimulus-Responsive Pirfenidone Liposomes for Pulmonary Delivery During Treatment of Idiopathic Pulmonary Fibrosis - Han, Meishan; Song, Yingjian; Liu, Sha; Lu, Xiaoyan; Su, Linyu; Liu, Meixuan; Zhu, Xiaosu; Sun, Kaoxiang; Lu, Yanan; Wang, Aiping (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is an interstitial lung disease characterized by progressive and irreversible loss of lung function. Clinically safe and efficacious drug treatments for IPF are lacking. Pirfenidone (an anti-inflammatory, antioxidant and anti-fibrotic small-molecule drug) is considered a promising treatment for IPF. Unfortunately, several disadvantages of pirfenidone caused by traditional administration (e.g., gastrointestinal reactions, short elimination half-life) hinder its implementation. We designed pirfenidone pH-sensitive liposomes (PSLs) to target the acidic microenvironment of IPF and act directly at the disease site through pulmonary administration. Pirfenidone was encapsulated in liposomes to extend its half-life, and modified with polyethylene glycol on the surface of liposomes to improve the permeability of the mucus layer in airways. In vitro, the cytotoxicity of pirfenidone PSLs to pulmonary fibroblasts was increased significantly at 48 h compared with that using pirfenidone. In a murine and rat model of bleomycin-induced pulmonary fibrosis, pirfenidone PSLs inhibited IPF development and increased PSL accumulation in the lungs compared with that using pirfenidone solution or phosphate-buffered saline. Pirfenidone PSLs had potentially fewer side effects and stronger lung targeting. These results suggest that pirfenidone PSLs are promising preparations for IPF treatment.